Kepuasan Mahasiswa Terhadap Pelayanan Administrasi Akademik Fakultas Ilmu Ekonomi Dan Bisnis Universitas Muhammadiyah Lamongan - Abdul Majid; Ratna Nurdiana; Ninik Mas’adah; Erna Nur Faizah; Suryani Yuli Astuti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
This study aimed at determining students' satisfaction toward the BAAK FEB UMLA service based on tangibles, responsiveness, reliability, empathy, and confidence. This research was a descriptive study with a quantitative approach. The population of this research was semester II students of Accounting and Management Study Program 2019-2020 as many as 41 students. The samples were obtained through Total Sampling. The data collection technique was attitude scale. Then the data were analyzed using trend test and percentage of a frequency distribution. The results of this study indicated: 1) Students' Satisfaction based on Tangibles aspects was 74.62%, 2) Students' Satisfaction based on Responsiveness aspects was 61.86%, 3) Students' Satisfaction based on Reliability aspects was 72.96%, 4) Students' Satisfaction based on Empathy aspects was 71.77%, 5) Students' Satisfaction based on Assurance aspects was 70.80%.